PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH PADA PEMBELAJARAN TEMA âINDAHNYA NEGERIKUâ KELAS IV SD NEGERI BOLO DEMAK TAHUN PELAJARAN 2013/2014 - Fariz Ardian Prasetya, Mei Fita Asri Untari, (MALIH PEDDAS, 2014)
Learning of SD Negeri Bolo Demak had never used Make A Match learning model. The teachers only use discussion in every learning. The low of variant learning model usage effects for less optimum learning process. Problem of this research, how is the application of Make A Match learning model for the theme of learning âIndahnya Negerikuâ for forth grade of SD Negeri Bolo Demak in 2013/2014? The purpose of this research is, to describe the application of Make A Match model learning in theme of learning âIndahnya Negerikuâ for forth grade of SD Negeri Bolo Demak in 2013/2014. This research uses descriptive qualitative research approach. Location of the research is in SD Negeri Bolo Demak for forth grade on 2nd semester. Data is sourced by the words of research result. The result of research shows there is increase of student evaluation in learning of 4, 5, and 6 uses Make A Match learning model in theme of learning âIndahnya Negerikuâ. The average of classical has increase until 86,7% which the result is better than classical limit above 75% of all students. The result of teacher learning observation uses Make A Match learning model, has the average with âgoodâ criteria until 64,2%. The observation result of studentâs attitude shows there is increase the studentâs attitude change in 6th learning, there are 26 students from 30 students or it has 86,7% completeness classically with very good criteria. Students and teacherâs response to the learning uses Make A Match learning model is, most of all students very happy, interested and more active in the learning. Suggestion the researcher given, it will be better if the teacher uses Make A Match learning model in the learning, students are better to study well, so the learning can be done conducively.